Efeitos da inibição reversível do hipotalamo dorsomedial e da porção dorsal do hipotálamo ventromedial sobre respostas comportamentais de defesa - Nascimento, Juliana Olivetti Guimarães [UNIFESP] (2010)
Previous evidence indicates that the medial hypothalamus is part of a neurobiological substrate controlling defensive behavior. In particular, it has been shown that a hypothalamic nucleus, the dorsomedial hypothalamus (DMH), is involved in the regulation of escape, a defensive behavior related to panic attacks. The role played by other hypothalamic nuclei in the organization of fear-related responses however is less clear. In this study we addressed this question by investigating the effects of the reversible inactivation of two hypothalamic nuclei, the DMH and the dorsomedial part of the ventromedial hypothalamus (VMHdm), on escape behavior generated in male Wistar rats by an ethologically relevant threatening stimulus: the exposure of rats to the open arms of the elevated T-maze. Results showed that intra-DMH administration of the GABAA receptor agonist muscimol (0.5 nmol and 1.0 nmol/0.2 μl) inhibited escape behavior, suggesting an antiaversive effect, although the higher dose also altered locomotor activity in an open field. Muscimol intra-DMH did not affect elevated T-maze inhibitory avoidance, a behavior associated with generalized anxiety disorder. On the other hand, muscimol intra-VMHdm did not alter either avoidance or escape measurements. Also, intra-DMH administration of the sodium channel blocker lidocaine (1 nmol/0.2 μl) was without effect, what is probably related to the fact the lidocaine, unlike muscimol, also inactivate fibers of passage and not only cell bodies. Taken together, our data corroborate previous evidence suggesting that the DMH is involved in the modulation of escape. Dysfunction of this regulatory mechanism may be of relevance in the genesis/maintenance of panic disorder.